Transgenerational consequences of maternal immune activation. (January 2020) - Pollak, Daniela D.; Weber-Stadlbauer, Ulrike
Abstract: Prenatal exposure to infectious or inflammatory insults is increasingly recognized in the etiology of neuropsychiatric diseases, including schizophrenia, autism, depression and bipolar disorder. New discoveries highlight that maternal immune activation can lead to pathological effects on brain and behavior in multiple generations. This review describes the transgenerational consequences of maternal immune activation in shaping brain and behavior anomalies and disease risk across generations. We discuss potential underlying mechanisms of transmission, by which prenatal immune activation can mediate generation-spanning changes in brain development and functions and how external influences could further determine the specificity of the phenotype across generations. The identification of the underlying mechanisms appears relevant to infection-related neuropsychiatric illnesses independently of existing diagnostic classifications and may help identifying complex patterns of generation-spanning transmission beyond genetic inheritance. The herein described principles emphasize the importance of considering ancestral infectious histories in clinical research aiming at developing new preventive treatment strategies against infection-related neurodevelopmental disorders and mental illnesses.